2019
DOI: 10.1002/joc.6108
|View full text |Cite
|
Sign up to set email alerts
|

Near‐surface mean wind in Switzerland: Climatology, climate model evaluation and future scenarios

Abstract: Near‐surface seasonal and annual mean wind speed in Switzerland is investigated using homogenized observations, Twentieth Century Reanalysis (20CRv2c) data and raw model output of a 75 member EURO‐COoRdinated Downscaling EXperiment regional climate model (RCM) ensemble for present day and future scenarios. The wind speed observations show a significant decrease in the Alps and on the southern Alpine slopes in the period 1981–2010. However, the 20CRv2c data reveal that the recent trends lie well within the deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The intensity and duration of autumn mixing affect the dissolved oxygen concentration at ice‐on (Kirillin et al, 2012; Leppäranta, 2015). Like most inner Alpine valleys (Graf et al, 2018), Lake Tovel has little wind (Eccel & Toller, 2006), especially during late autumn (mean wind velocities < 0.5 m s −1 ). By mid‐November, Lake Tovel was usually isothermal or showed only weak thermal stratification as indicated by density‐based mixing indices.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity and duration of autumn mixing affect the dissolved oxygen concentration at ice‐on (Kirillin et al, 2012; Leppäranta, 2015). Like most inner Alpine valleys (Graf et al, 2018), Lake Tovel has little wind (Eccel & Toller, 2006), especially during late autumn (mean wind velocities < 0.5 m s −1 ). By mid‐November, Lake Tovel was usually isothermal or showed only weak thermal stratification as indicated by density‐based mixing indices.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that the Alpine region (AL, purple color) presents the lowest mean values, with an overall ERA5 underestimation, together with the larger overestimated cut-in and light wind hours. This result is related to the difficulties for modelled wind to accurately describe the atmospheric dynamics over these mountainous areas [8,17,71,72]. To reduce such biased results could be obtained using higher resolution modelling simulations [19].…”
Section: Comparison Between Low Wind Conditions From Era5 and Observa...mentioning
confidence: 99%
“…Europe is a challenging region for wind studies, due to the presence of numerous areas of complex orography. Several studies [3,[9][10][11][12][13] have analysed the basic wind speed statistics and have shown the importance of the spatial and temporal resolution of climate models for wind modelling, as can be seen in the analysis of coastal winds [14,15], or areas with orographic complexity [8,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years a number of compound extremes have been investigated. For instance, several studies have analysed the dependence between storm surge and heavy precipitation (Wahl et al, 2015;Zheng et al, 2013;Bevacqua et al, 2019) or extreme runoff (Ward et al, 2018;Hendry et al, 2019) to estimate the risk of compound flooding in coastal areas. Compound droughts and heatwaves have been studied for dif-ferent regions and varying temporal scales (Mazdiyasni and AghaKouchak, 2015;Zscheischler and Seneviratne, 2017;Manning et al, 2019;Sutanto et al, 2020;Zscheischler and Fischer, 2020).…”
Section: Introductionmentioning
confidence: 99%